KAJIAN KUAT TEKAN BETON SELF COMPACTING CONCRETE HASIL PENGEBORAN INTI VARIASI PENGAMBILAN ARAH VERTIKAL DAN HORIZONTAL - Valentana Ardian Tarigan; Immanuel Panusunan Tua Panggabean (Universitas Quality, 2020)
Buildings that use concrete as a structural material are faced with certain compressive strength requirements that are used as design standards. It is a fact that is always found in the field that the quality of the installed concrete cannot always be maintained at the target quality standard. The regulation that becomes the reference for Indonesian concrete standards, namely SNI 2847: 2013 requires that the test standard of core drilling is if the certainty of the low compressive strength value of concrete is known and the calculation results show that the load-bearing capacity is significantly reduced, then the core concrete test (cores) is allowed. taken from the area in question according to ASTM C42M. In such cases, three specimens shall be taken for each compressive strength test which falls below the given value. The test was carried out using a diameter of 4